Effect of magnesium rich synthetic gypsum application on ultisol properties and growth of oil palm seedlings - Ayanda, Arolu Fatai (2017)
Oil palm cultivation in Malaysia is mainly on the acidic Ultisols and Oxisols, which are highly weathered with low fertility. Despite the problem of low soil productivity, the good physical makeup of the soil makes them suitable for sustainable oil palm cultivation. This study consisted of two parts. The first study was a field work conducted in an oil palm plantation at Bera, Pahang, in an attempt to classify the dominant soil types in the area and to determine their suitability for oil palm cultivation. The second study was a glasshouse trial at Universiti Putra Malaysia using oil palm seedlings planted in polybags, containing Ultisols collected the oil palm plantation. For the field study, a soil pit was dug for profile description on soil morphological characteristics, and samples were collected based on genetic horizons for analyses. Only one soil series was identified in the area under study. The main objective of this study was to evaluate the performance of magnesium rich synthetic gypsum (MRSG) obtained from a rare earth refining company in Malaysia (Gebeng, Pahang) as a potential magnesium source in fertilizer programme for sustainable oil palm cultivation in Malaysia. The soil under study was formed under tropical environment with udic moisture regime on fine-grained sedimentary rocks, mixed with tuffs of Permian age. The soil in the area was reddish in colour, clayey, deep and highly weathered. The clay fraction of the soil was dominated by kaolinite, gibbsite, goethite, and hematite; thus, the plant nutrient status of the soil is low. The exchangeable aluminium in the soil was low, although the soil has an acidic reaction in water. Taxonomically, the soil was classified as Clayey Kaolinitic, isohyperthermic, Typic Paleudult due to its colour and the presence of diagnostic argillic horizon in the B-horizon (Bt). From the results of this study, it was deduced that the inherent soil properties in the field situation had no significant limitation for oil palm cultivation; hence, with proper agronomic practices, the area can be utilized for sustainable oil palm cultivation.In meeting up with the world demand for oil palm products, the industry needs to sustain high productivity. This requires regular application of high amount of fertilizers, one of which is Mg-fertilizer. A glasshouse study for 9 months, using oil palm seedlings, was conducted to examine the effectiveness of MRSG as a source of Mg for oil palm cultivation. In this study, plant performance, nutrient uptake, soil chemical characteristics, and population of soil microbes in comparison with other Mg fertilizer sources, such as ground magnesium limestone (GML) and kieserite (MgSO4.7H2O) were determined. The experimental design was Randomized Completely Block, with 7 treatments and 6 replications, the treatments were: T1- NPK without source of Magnesium; T2 - NPK + Kieserite at standard rate; T3 - NPK + GML at standard rate; T4 - NPK + MRSG at the recommended rate; T5 - NPK + MRSG at one-half the recommended rate; T6 – NPK + MRSG at double the recommended rate; T7 - NPK+ MRSG to equivalent amount of Ca in GML. Soil parameters at 0, 3, 6 and 9 months measured were pH, EC, exchangeable cations, carbon, nitrogen, sulphur and selected micronutrients, while the plant parameters were growth traits, fresh and dry biomass of the seedlings root and above ground portion, macronutrients (Ca, Mg, P, and K) and micronutrient (Zn and Mn). Results showed that there were significant responses among soil to treatments; Treatment (T7) containing 36 gram of Mg i.e MRSG applied at double the recommended rate of magnesium required by oil palm seedlings showed the highest increase of soil pH (6.82), exchangeable calcium (1.52 cmolc/ kg), magnesium (0.59 cmolc/ kg) and total sulphur (0.07 %) in the soil, while the above-measured parameters were lowest in control. The exchangeable aluminium of the soil was low as soil pH under field condition was above 5. GML treatment (T3) was able to increase soil pH that helped enhance oil palm growth. It was found that kieserite (MgSO4.7H2O) treatment had a significant effect on soil fertility, especially in terms of increase in exchangeable magnesium and total sulphur. It was found that MRSG treatments (T4, T5, T6 and T7) had positive effect on soil fertility, shown by the increase in exchangeable Mg, Ca and soil pH. MRSG application did not have negative effect on microbial activities in the soil. Due to the improved soil fertility, the growth of the oil palm seedlings in terms of height, bole diameter, chlorophyll index and root performance was as good as those planted on soil treated with GML or kieserite. As such, Magnesium rich synthetic gypsum can replace kieserite as Mg source for immature oil palm cultivation.